Performance of LR-type solid-state fault current limiter in improving power quality and transient stability of power network with wind turbine generators. (January 2016) - Fereidouni, Alireza; Masoum, Mohammad A.S.; Hosseinimehr, Tahoura; Moghbel, Moayed
Highlights: We model an inductive–resistive-type solid state fault current limiter (SSFCL-LR). We examine the performance of SSFCL-LR on an electric power network with the doubly-fed induction generator wind-turbine (DFIG-WT). We use a prototype experimental setup to validate the operation of SSFCL-LR in practice. Employing SSFCL-LR will effectively suppress the fault currents. Employing SSFCL-LR can also contribute in maintaining the instantaneous voltages of IG-WTs and DFIG-WTs under any short-circuit faults. Abstract: Distributed generations (DGs) are predicted to perform an increasing role in the future power system. Expose of DGs can change the fault current during a grid disturbance and disturb the existing distribution system protection. Solid-state fault current limiters (SSFCLs) can provide a quick system protection during severe faults and are expected to advance the reliability and stability of the power system. SSFCLs are categorized into R - (resistive) and L - (inductive) types by the fault current limiting impedance. An L -type SSFCL is more effective in suppressing the voltage drop during faults. On the other hand, an R -type SSFCL is more effective in consuming the acceleration energy of generators during faults. Therefore, applying both functions lead to the improvement of the power quality and transient stability of the power system. This paper aims to investigate the performance of an inductive–resistive-type solid state fault current limiter (SSFCL-LR) that captures the features and advantages of inductive SSFCLs (SSFCL-Ls) and resistive SSFCLs (SSFCL-Rs) on an electric power network with the doubly-fed induction generator wind-turbine (DFIG-WT), which is a representative renewable energy source. Its connection to a power network simply increases the short-circuit current during a fault toward its maximum nominal level, which is closer to the rating of the circuit breaker, when compared to the case without the DFIG-WT system. This can aggravate the reliability of the overall power system. Detailed laboratory experiments and simulations are performed to demonstrate the capability of SSFCL-LR in simultaneously controlling the fault current, improving the power quality and enhancing the transient stability of the IEEE benchmark four-machine two-area system with induction generator wind turbines (IG-WT) and DFIG-WTs. PSCAD/EMTDC was used in order to analyze the power system characteristics of the SSFCL-LR unit.